2021
DOI: 10.1016/j.jcte.2021.100276
|View full text |Cite
|
Sign up to set email alerts
|

Obesity in cystic fibrosis

Abstract: The prevalence of obesity in patients with cystic fibrosis (CF) is increasing and around one-third of adults with CF are now overweight or obese. The causes of excess weight gain in CF are likely multifactorial, including: adherence to the high-fat legacy diet, reduced exercise tolerance, therapeutic advances, and general population trends. Increased weight has generally been considered favorable in CF, correlating with improved pulmonary function and survival. While the optimal BMI for overall health in CF is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 54 publications
0
34
0
Order By: Relevance
“…Due to the diversity of studies and patient characteristics, it must be assumed that the prevalence of OSA is often underestimated, and further studies are needed to confirm our findings. This assumption is supported by the fact that the CF population is aging due to improved treatment options and obesity is an increasing problem [ 4 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the diversity of studies and patient characteristics, it must be assumed that the prevalence of OSA is often underestimated, and further studies are needed to confirm our findings. This assumption is supported by the fact that the CF population is aging due to improved treatment options and obesity is an increasing problem [ 4 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the diversity of studies and patient characteristics, it must be assumed that the prevalence of OSA is often underestimated, and further studies are needed to confirm our findings. This assumption is supported by the fact that the CF population is aging due to improved treatment options and obesity is an increasing problem [4,36]. Outside the field of CF, the co-existence of OSA and chronic obstructive airflow limitation (OSA-COPD overlap syndrome) has received increasing attention in recent years.…”
Section: Discussionmentioning
confidence: 99%
“…We have also observed an increase in the proportion and number of PwCF who are overweight or obese associated with the availability of CFTR modulators. Such patients may experience other health consequences associated with obesity (e.g., hypertension, cardiovascular disease, type 2 diabetes mellitus, obstructive sleep apnea) [15] . PwCF taking modulators have also experienced liver function abnormalities, increased anxiety and depression, and rashes.…”
Section: The Changing Care Needs Of People With Cfmentioning
confidence: 99%
“…A study of longitudinal changes in nutrition using BMI values over a 10-year period has reported that underweight CF patients decreased from 20.6% to 11.1%, while overweight/obese CF patients increased from 7% to 18.4% [ 36 ]. Most of our patients were found to be in the normal weight group, where the BMI is between 19 and 25, which is very important for better lung function.…”
Section: Discussionmentioning
confidence: 99%